Adoption of Strategic Management Accounting and Its Effect on Banks’ Perceived Performance in Nepal - Narayan Maharjan, Purna; Giri, Neeru; Thapa, Barsha (MVIC Journal of Management and Information Technology, 2025)
This study investigates adoption of Strategic Management Accounting (SMA) techniques and their impact on Perceived Organizational Performance (POP) of Nepalese banks. SMA extends traditional management accounting by incorporating strategic and competitive information, enabling more informed decision-making and better alignment with long-term goals. Data were collected from 225 respondents, including branch managers and accounting officers, using structured questionnaires and analyzed through descriptive statistics and Structural Equation Modeling (SEM). The results reveal that SMA adoption explains 74% of variance in perceived performance, with competitor analysis and benchmarking being the most widely adopted techniques. In contrast, strategic pricing and value-chain costing are less used due to regulatory constraints and limited cost-tracing capabilities. The study confirms a significant positive effect of SMA adoption on POP of Nepalese banks, consistent with global findings and supported by Contingency Theory. The implications suggest that enhancing SMA adoption can improve both financial and non-financial outcomes in Nepalese banks and potentially in other sectors.